1996
DOI: 10.3168/jds.s0022-0302(96)76597-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cell-Wall Digestion of Orchardgrass and Alfalfa Silages Treated with Cellulase and Formic Acid

Abstract: The objectives of this study were to determine the effects of cellulase (from Trichoderma longibrachiatum) combined with formic acid, applied before ensiling, on the subsequent concentration and composition of the cell wall and on the extent and rate of in situ cell-wall digestion of orchardgrass (Dactylis glomerata L.) and alfalfa (Medicago sativa L.). Treated and control forages of both plant species were ensiled for at least 60 d before being ruminally digested by two fistulated cows. Analyses of NDF, ADF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
14
3
Order By: Relevance
“…Results of Italian ryegrass silage were mostly in agreement with those of Van Vuuren et al, 10 who found that enzyme treatment increased the rapidly degradable organic matter and reduced the rate of cellulose degradation in perennial ryegrass silage. Nadeau et al 13 reported smaller effects on legume (lucerne) than on grass (cocksfoot) silage, whereas the response in this study appeared greater when the legume crop was treated. Unlike the ®ndings of Hoffman et al, 9 both the amount and rate of NDF degradation were reduced in enzyme-treated lucerne silage.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Results of Italian ryegrass silage were mostly in agreement with those of Van Vuuren et al, 10 who found that enzyme treatment increased the rapidly degradable organic matter and reduced the rate of cellulose degradation in perennial ryegrass silage. Nadeau et al 13 reported smaller effects on legume (lucerne) than on grass (cocksfoot) silage, whereas the response in this study appeared greater when the legume crop was treated. Unlike the ®ndings of Hoffman et al, 9 both the amount and rate of NDF degradation were reduced in enzyme-treated lucerne silage.…”
Section: Discussioncontrasting
confidence: 51%
“…Although several workers examined the effect of enzymes on the in situ degradation of silages, the results were variable and did not reach agreement. 9,10,12,13 The response to enzyme treatment may be different between grasses and legumes owing to certain differences in their composition and digestion of cell wall components. However, information is apparently scarce on the fermentation and digestion of enzyme-treated silages prepared from the two forage species.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, T3 silage had a lower aNDF concentration as compared to T2 silage, suggesting that plant cell wall carbohydrates within aNDF were hydrolysed by fibrolytic enzymes during the ensiling process. A reduction in aNDF concentration is a typical response of applying fibrolytic enzyme at ensiling on various forages as a result of hemicellulose and cellulose being partially hydrolysed during ensiling (Nadeau et al, 1996(Nadeau et al, , 2000Kung and Ranjit, 2001). This is supported by the observation that the rapidly degradable fraction of DM increased but the total fiber digestibility decreased in T3 treated silage in later in situ study.…”
Section: Effects Of Silage Additives On Ensiling Chemical Compositiosupporting
confidence: 57%
“…Addition of exogenous fibrolytic enzyme (i.e., cellulases and xylanases) along with inoculants has been explored as another strategy to improve the digestibility of fiber in silage (Jaster and Moore, 1988;Nadeau et al, 1996;McAllister et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…This indicates that those exogenous enzymes attached to the substrate before the native enzymes (Colombatto et al, 2003) to degrade a greater extent of NDF, and to increase the potentially digestible fraction (Nadeau et al, 1996). It is also possible that exogenous enzymes promote lignin solubility, reducing the indigestible fraction.…”
Section: Discussionmentioning
confidence: 99%